2015
DOI: 10.1002/2014jd022378
|View full text |Cite
|
Sign up to set email alerts
|

Airborne measurements of organosulfates over the continental U.S.

Abstract: Organosulfates are important secondary organic aerosol (SOA) components and good tracers for aerosol heterogeneous reactions. However, the knowledge of their spatial distribution, formation conditions, and environmental impact is limited. In this study, we report two organosulfates, an isoprene-derived isoprene epoxydiols (IEPOX) (2,3-epoxy-2-methyl-1,4-butanediol) sulfate and a glycolic acid (GA) sulfate, measured using the NOAA Particle Analysis Laser Mass Spectrometer (PALMS) on board the NASA DC8 aircraft … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
133
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 117 publications
(156 citation statements)
references
References 88 publications
21
133
2
Order By: Relevance
“…IEPOX-SOA, while representing a type of SOA, was also not expected to be produced in the OFR. In the atmosphere, IEPOX-SOA is formed via reactive uptake of gas-phase IEPOX onto acidic aerosols Froyd et al, 2010;Surratt et al, 2010;Lin et al, 2012;Liao et al, 2015). As detailed in Hu et al (2016), IEPOX can be formed in the gas phase in the OFR at accelerated rates, but the rate of reactive uptake in the OFR does not increase with the increased OH concentrations, resulting in negligible formation of IEPOX-SOA in the OFR.…”
Section: Positive Matrix Factorization (Pmf) Of Soa After Oh Oxidationmentioning
confidence: 99%
“…IEPOX-SOA, while representing a type of SOA, was also not expected to be produced in the OFR. In the atmosphere, IEPOX-SOA is formed via reactive uptake of gas-phase IEPOX onto acidic aerosols Froyd et al, 2010;Surratt et al, 2010;Lin et al, 2012;Liao et al, 2015). As detailed in Hu et al (2016), IEPOX can be formed in the gas phase in the OFR at accelerated rates, but the rate of reactive uptake in the OFR does not increase with the increased OH concentrations, resulting in negligible formation of IEPOX-SOA in the OFR.…”
Section: Positive Matrix Factorization (Pmf) Of Soa After Oh Oxidationmentioning
confidence: 99%
“…7. IEPOX has been demonstrated to be an important precursor to ambient (Budisulistiorini et al, 2015; and laboratory-generated (Lin et al, 2012;Paulot et al, 2009) isoprene SOA leading to the formation of 2-methyltetrols , OS (Liao et al, 2015), and other species through aerosol phase reactions in which IEPOX products contribute up to 33 % of ambient OM in the southeast US . The formation of IEPOXderived SOA has been shown to be primarily from the reactive uptake in the presence of LWC and [H + ] but is most highly correlated with aerosol acidity (Gaston et al, 2014).…”
Section: Simulated Composition Of Isoprene Soamentioning
confidence: 99%
“…A very recent study revealed a previously unrecognized pathway for organosulfate formation through the heterogeneous reaction of SO 2 with the unsaturated bond in oleic acid (Shang et al, 2016). A number of biogenic organosulfates have been observed in ambient aerosol, in particular, isoprene-derived organosulfates (e.g., Kristensen et al, 2011;He et al, 2014;Liao et al, 2015;Budisulistiorini et al, 2015). A recent study reported the formation of aromatic organosulfates by photochemical oxidation of polycyclic aromatic hydrocarbons (PAHs) in the presence of sulfate seed particles (Riva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies of organosulfates have remained at the qualitative level, although a limited number of studies have provided quantitative or semi-quantitative analysis of certain organosulfates (e.g., Kundu et al, 2013;Staudt et al, 2014;Ma et al, 2014;Olson et al, 2011;Hettiyadura et al, 2017). Moreover, several studies show that organosulfates are present as a wide range of species with individual species such as the organosulfate derived from isoprene epoxydiols (IEPOXs) contributing 0.2-1.4 % of the total organic aerosol mass (Liao et al, 2015). This further complicates the quantification of organosulfates.…”
Section: Introductionmentioning
confidence: 99%